REMARKETING MEDIA ALTERNATIVES BASED ON CUSTOMER PREFERENCES - Adhatus Solichah Ahmadiyah; Faridatul Aidah; Navinda Meutia; Denise Rahmadina; Daniel Lumbantobing; Ratih Anggraini (JUTI: Jurnal Ilmiah Teknologi Informasi, 2020)
Remarketing is a powerful tool for marketers to offer products over and over to existing customers or potential customers. By using remarketing, the marketers target to further down their sales funnel. As in traditional marketing, most online marketers find it challenging to deliver the best way of advertising their products according to what customers need or like. This research aims to achieve the right promotional media alternatives based on customer preferences. A clustering method was used to perform behavior segmentation on sales data. Then, customer reviews on the purchased products collected from online platforms were analyzed to obtain customer preferences. Finally, customer preference was mapped to some suitable promotion media. The experiment result showed that pipelining sales data and product reviews could obtain definite and distinct promotional media based on customer preference. Overall, this research may help online marketers bundle specific remarketing content into promotional media that matches to customer favorites.